The Impact of the Russian-Ukrainian War on Europe's Forest-Based Bioeconomy - Hans Lööf; Andreas Stephan (Vierteljahrshefte zur Wirtschaftsforschung, 2022)
The Russian-Ukrainian war has led to an increase of stress on forests. International sanctions have hit timber exports from Russia and Belarus, and the conflict severely affects timber production in Ukraine. The three countries accounted for a quarter of the worldwide timber trade in 2021, and Russia was the world's largest exporter of softwood. The war increases the European Union's (EU's) dependency on its own forest resources. This exacerbates the challenge to achieve a balance between forests as carbon sink, habitat for biodiversity conservation and functional ecosystems on one hand, and on the other, the growing demand for wood-based materials harvested from forests and rising demand for renewable energy. Our study provides insights into this trade-off with regard to climate goals, where EU's forest-based bioeconomy plays a major role. – – Der russisch-ukrainische Krieg verstärkt die Belastung der Wälder. Internationale Sanktionen treffen Exporte aus Russland und Weißrussland, und der Krieg beeinträchtigt die Holzwirtschaft in der Ukraine stark. Diese drei Länder machten im Jahr 2021 zusammen ein Viertel des weltweiten Holzhandels aus, und Russland war der weltweit größte Exporteur von Nadelholz. Der Krieg erhöht die Abhängigkeit der Europäischen Union (EU) von den eigenen Waldressourcen. Dies erhöht die Herausforderung, ein Gleichgewicht zwischen Wäldern als Kohlenstoffsenke, als Lebensraum für den Erhalt von Biodiversität und als funktionale Ökosysteme einerseits und der wachsenden Nachfrage nach Holz und erneuerbaren Energien andererseits zu erreichen. Dieser Artikel gibt Einblicke in das mögliche Dilemma im Hinblick auf die Erreichung des formulierten Klimaziels der EU, für welches die forstbasierte Bioökonomie eine wichtige Rolle spielt.
Keywords: F18; L73; H70; Q54; Q57; 330; Bioeconomy; biodiversity; climate-change; forest management; sustainability